Incidence and risk factor of postpartum depressive symptoms in women: a population based prospective cohort study in a rural district in Bangladesh - Nasreen, Hashima E; Edhborg, Maigun; Petzold, Max; Forsell, Yvonne; Kabir, Zarina Nahar (OMICS Publishing Group, 2015)
Objective: Limited evidence exists on the incidence of postpartum depressive symptoms (PDS) in low-income countries. This study aims to determine the incidence of and risk factors for developing PDS in a cohort of women in rural Bangladesh. Methods: A total of 588 consecutive women were assessed during the last trimester of pregnancy, 2-3 and 6-8 months postpartum for depressive symptoms and for putative risk factors. The validated Bangla version of Edinburgh Postnatal Depression Scale was used to measure PDS. Background information was collected using a structured questionnaire at the respondents' homes. Multiple Cox's regression analyses identified risk factors of PDS. Results: The incidence proportion of PDS from third trimester of pregnancy to 2-3 months postpartum was 8.0%, and from 2-3 to 6-8 months postpartum 18.4%. Poor socioeconomic status (HR 2.62, 95% CI 1.83-3.73), physical partner violence during pregnancy (HR 1.65, 95% CI 1.08-2.50), anxiety symptoms during pregnancy (HR 1.69, 95% CI 1.16-2.46), and previous depressive symptoms (HR 2.95, 95% CI 1.80-4.84) were identified as risk factors. Conclusion: PDS are common, heterogeneous and largely undetected public health problem in Bangladesh. Screening for depressive symptoms in the last trimester of pregnancy or in the 6-8 months postpartum ought to be integrated into maternal and child health programmes. Intervention to reduce depressive symptoms during postpartum needs to target those women who are poor, experienced violence during pregnancy, had anxiety symptoms during pregnancy, and had a previous history of depressive symptoms.